2018
DOI: 10.1371/journal.pone.0201551
|View full text |Cite
|
Sign up to set email alerts
|

MiR-18a regulates myoblasts proliferation by targeting Fgf1

Abstract: MiRNAs play an important role in cell proliferation, apoptosis, and differentiation. MiR-18a is increasingly being recognized as a regulator of cancer pathogenesis. Here, we discovered that miR-18a participates in myoblasts proliferation. Expression of miR-18a was downregulated with the differentiation of C2C12 myoblasts. Overexpression of miR-18a affected the proliferation of C2C12 cells, primary myoblasts and RD cells. MiR-18a influenced the expression of cell cycle-related genes. Using TargetScan 6.2, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“… 7 A series of in vitro and in vivo studies have demonstrated that miR-18a plays an important role in different cell functions via downregulating FGF1, Smad4, HIF-1α, and other target genes. 12 , 13 , 14 Therefore, elucidation of the underlying mechanisms by which miR-18a regulates the functions of trophoblast cells may provide a better understanding of the pathophysiology of this disorder and uncover new targets for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“… 7 A series of in vitro and in vivo studies have demonstrated that miR-18a plays an important role in different cell functions via downregulating FGF1, Smad4, HIF-1α, and other target genes. 12 , 13 , 14 Therefore, elucidation of the underlying mechanisms by which miR-18a regulates the functions of trophoblast cells may provide a better understanding of the pathophysiology of this disorder and uncover new targets for therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…These miRNAs have important roles in muscle differentiation, development and atrophy (3335), and are predicted to participate in the regulatory networks of myogenesis, muscle fiber type composition, muscle growth and homeostasis (33). The miRNAs associated with muscle differentiation, development and muscular atrophy include miR-133a (36,37), miR-133b (38), miR-206 (39,40), miR-186 (41), miR-23a (42,43), miR-27b (44), miR-29b (32), miR-1a (39) and miR-18a (45,46). miR-1 promotes myoblast differentiation and regeneration (36,37,39,47).…”
Section: Introductionmentioning
confidence: 99%
“…Also, in the developing mouse neocortex, the miR-17-92 cluster, which includes miR-18a, has been shown to promote proliferation of neuronal progenitors [50]. Interestingly, however, miR-18a has also been shown to suppress cell proliferation in other contexts such in pancreatic progenitor cells [47] and myoblast cells [51], and even has anti-proliferation/anti-tumor effects in colorectal and breast cancers [52,48,53]. The effects of miR-18a on the cell proliferation are, therefore, dependent on the cell type and injury/disease state of the tissue involved.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in the developing mouse neocortex, the miR-17-92 cluster, which includes miR-18a, has been shown to promote proliferation of neuronal progenitors [50]. Interestingly, however, miR-18a has also been shown to suppress cell proliferation in other contexts such in pancreatic progenitor cells [47] and myoblast cells [51], and even . CC-BY-NC-ND 4.0 International license available under a was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%